Formulating The Concept of Mufassir - Zamakhsyari bin Hasballah Thaib; Mukhamad Hadi Musolin; Vina Annisa (Waraqat: Jurnal Ilmu-Ilmu Keislaman)
Establishing the concept of a mufassir is an important issue that greatly influences the understanding of the character of those who perform tafsir as well as the criteria and distinctive features of their work. This discussion is also related to determining the levels of mufassir and the criteria that distinguish who belongs to this category and who does not. Unfortunately, this concept has not received adequate attention in heritage studies, and contemporary efforts to explore this issue are still limited and often face various challenges. This article aims to present a critical analysis in formulating the concept of mufassir, so that the forms of tafsir work that qualify someone to be recognized as a mufassir can be identified. Furthermore, this article will discuss the categorization of mufassir and provide a general explanation of their levels based on the methods they employ. This research is based on library study with a critical analytical approach. Among the results of this research, there are two main points:(1) The work of tafsir has various forms and does not exist at the same level, which generally includes various categories such as author of tafsir works, explainer of the difference between correct and weak understandings, compiler of tafsir materials, summarizer of tafsir works, explainer of tafsir works, teacher of tafsir, and transmitter of tafsir; (2) The use of the term mufassir allows for a lot of tolerance, where generally mufassir can be categorized into two groups, namely practical mufassir and participatory mufassir